Efeito do flavonoide galangina sobre a susceptibilidade às convulsões induzidas por pentilenotetrazol na presença de prostaglandina E2 - Zorzi, Viviane Nogueira de (2018)
Epilepsy is one of the most common chronic neurological diseases, characterized by recurrent epileptic seizures, where one-third of patients are refractory to existing treatments. Evidences have revealed association between neuroinflammation and increased susceptibility to seizures since there is a pronounced increase in the expression of key inflammatory mediators, such as prostaglandin E2 (PGE2) during seizures. The PGE2 has been demonstrated to stimulate the release of glutamate and to inhibit Na+ K+ -ATPase enzyme, which in fact may increase neuronal excitability, contributing to seizure. Knowing the important role of inflammation during seizures and existence of refractory to anticonvulsant treatment, the purpose initial of the present study was to investigate whether PGE2 increases to susceptibility to seizures induced by pentylenetetrazol (PTZ). Subsequently, we evaluate whether a compound isolated from the Piper aleyreanum plant, named Galangin, proved to be anti- inflammatory and protective in a nociception model induced by glutamate and PGE2, could have anticonvulsive activity in this study. For this, in the experiment 1, the mice were injected with PGE2 (100ng/2μl; intracerebroventricular (i.c.v.) and fifteen minutes later were injected with a subefective PTZ dose (35mg/kg, intraperitoneal (i.p) for evaluation of susceptibility to seizures. In the experiment 2, the mice were injected with Galangin (30mg/kg; i.p.) fifteen minutes before PGE2 injection, fifteen minutes later were injected with PTZ, in the same doses. Our results showed that the group treated com PGE2 increased the susceptibility to PTZ, causing myoclonic and generalized seizures, increasing the seizures duration and electroencephalographic wave amplitude. Furthermore, statistical analyzes showed that the treatment with PGE2 or PGE2 and PTZ combined increased IBA-1 (microglial marker), GFAP (astrocytic marker), 4-HNE (lipid peroxidation marker), VCAM-1 (vascular cell adhesion molecule 1) and p-PKAIIα (phosphorylated cAMP-dependent protein kinase) immunocontents. However, nor PTZ or PGE2 treatment changed the immunocontent of receptors of PGE2 (EP1, EP2 and EP3). Indeed, pre-treatment with Galangin prevented the convulsive behavior and decreased electroencephalographic wave amplitude as well as prevented reactive species production, microglial and astrocytic activation, decreased VCAM-1 immunocontent and phosphorylation state of PKAIIα induced by PGE2/PTZ. Therefore, this study suggests that the compound Galangin presented anticonvulsive and anti-inflammatory activities against the behavioral and neurochemical changes induced by administration of PGE2 and PTZ. However, further studies are needed to investigate the clinical implications of these findings and their underlying mechanisms.